Dr med. Jolanta Pieńkowska-Mikołajczyk (1927-1996) — pediatra, pionier poznańskiej endokrynologii dziecięcej. Wspomnienie - Krawczyński, Marian (Pediatria Polska - Polish Journal of Paediatrics, 2017)
The biography of Jolanta Pieńkowska-Mikołajczyk MD, PhD, an universally educated pediatrician of Poznań is presented. In particular, the traits of her personality, professional way and scientific achievements in a new, developing area - pediatric endocrinology - are depicted. She was professionally active from the fifties to the eighties of the 20th century.